Urgensitas Kompetensi Guru Agama Kristen terhadap Pendidikan Karakter Kristiani Berdasarkan Kurikulum 2013 - Esta Silitonga; Djoys Anneke Rantung; Lamhot Naibaho (Departement of Mathematics Education, 2023)
The urgency of the competence of Christian religion teachers for Christian character education based on the 2013 curriculum has become an increasingly important topic today. Where teacher competence is assessed by various groups as a professional description of whether or not educators (teachers) are. Even teacher competence has an influence on the success achieved by students. Capability is the result of a combination of education, training, and experience. The purpose of this study was to identify Christian characters associated with the use of the 2013 curriculum in an effort to strengthen the urgency of Christian religion teacher competence for Christian character education based on the 2013 curriculum. This study used a qualitative approach by conducting a literature review and analysis of relevant data. The results of this study indicate that the urgency of the competence of Christian religion teachers for Christian character education based on the 2013 curriculum, provides student and teacher involvement, and provides a variety of resources. This study underscores the importance of careful thought and careful planning in implementing the urgency of Christian religion teacher competence for Christian character education based on the 2013 curriculum.